Nutritional risk at hospital admission and its long-term impact on COVID-19 survivors in Ha`il region, Saudi Arabia - Bin Ammar, Al Bandari; Eltoum, Nagat; Elkhalifa, Abd Elmoneim; Fatima, Sayeda; Elhussein, Nagwan; Soundararajan, Leo; Alkhalaf, Majid; Elshazley, Momen; Jalloun, Rola; Seifeldin, Sara; Al-Faqiri, Ghosoun; Al Shammari, Ritaj (Progress in Nutrition, 2025)
Background and aim: This study aims to investigate the relationship between nutritional risk at hospital admission and its effect on severe outcomes and length of hospital stay in hospitalized COVID-19 patients, both with and without comorbidities. Methods: This prospective cohort study included 103 COVID-19 patients hospitalized at King Salman Specialist Hospital in the Ha’il region of Saudi Arabia. Of 600 eligible patients contacted, 103 consented to participate, representing one of the first comprehensive investigations of nutritional risk in COVID-19 survivors in this region. Retrospective data were obtained from patient records at admission, covering sociodemographic details, clinical characteristics, symptoms, anthropometric measurements, nutrition-related laboratory results, and length of hospital stay. The Malnutrition Screening Tool was used to evaluate malnutrition risk at admission and follow-up, while body mass index was calculated using height and weight measurements taken at these time points. Results: Body mass index was not uniformly observed across all categories. Significant increase in Calcium (p-value 0.0001) was noted between admission and follow-up visits in COVID-19 patients. Ferritin levels were significantly decreased and associated with admission and follow-up only in patients without comorbidities (p-value 0.002). Although albumin levels differed significantly across all participants (p-value 0.0001), total protein levels did not show significant variation in comorbidities group. Additionally, moderate disease severity was strongly associated with longer hospital stays (p-value 0.0001). Conclusion: Several factors, including abnormal biomarkers and moderate case severity, were identified as potential influences on nutritional risk at hospital admission and its long-term effects on COVID-19 survivors.